Development of a power tiller operated paddy transplanter for conventional seedlings - PRAKASH K. V; Dr. M Sivaswami (Gudie) (Tavanur 1995 Kelappaji College of Agricultural Engineering and Technology)
Development of a power tiller operated paddy transplanter for conventional seedlings
Development of a power tiller operated paddy transplanter for conventional seedlings